Study the HLA Genotyping in Pulmonary Tuberculosis Patients in Babylon Province-Iraq - Mohammed A. K. Al-Saadi (Journal of Global Pharma Technology, 2017)
This study aimed to investigate the role of Human Leucocyte Antigen (HLA-DRB1) alleles in susceptibility to pulmonary tuberculosis in Babylon/ Iraq population. Whole blood samples collected from 50 pulmonary tuberculosis patients who are admitting to consultant clinic for respiratory diseases in Hilla – Babylon province during the period from February 2016 to February 2017. Out of the pTB patients, there were 27 males and 23 females, the patients age range was 12-80 years. Sequence specific oligonucleotide (SSO) was used to genotyping HLA-DRB1.The distribution of HLA-DRB1 genotypes in 50 patients with pulmonary tuberculosis and 50 healthy controls studied. HLA-DRB1*13 was a significantly increased in pulmonary tuberculosis patients 48% as compared with healthy controls 16% while HLA-DRB1*15 was a significantly increased in healthy controls 24% as compared with pulmonary tuberculosis patients 6%.The genotyping of all HLA-DRB1alleles found more common in females 77% than males 23% from total number of patients. Also, HLA-DRB1*13 was more common in females 75% than males 25% with pulmonary tuberculosis patients while HLA-DRB1*15 was common in females 100% and no appeared in males.Keywords: Pulmonary Tuberculosis, HLA-DRB1, SSO.